2006
DOI: 10.1038/sj.ki.5000130
|View full text |Cite
|
Sign up to set email alerts
|

Interacting molecule of AT1 receptor, ATRAP, is colocalized with AT1 receptor in the mouse renal tubules

Abstract: The renin-angiotensin system in the kidney plays a critical role in the regulation of renal hemodynamics and sodium handling through the activation of vascular, glomerular and tubular angiotensin II type 1 (AT1) receptor-mediated signaling. We previously cloned a molecule that specifically bound to the AT1 receptor and modulated AT1 receptor signaling in vitro, which we named ATRAP (for AT1 receptor-associated protein). The purpose of this study is to analyze the renal distribution of ATRAP and to examine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 30 publications
0
88
0
1
Order By: Relevance
“…BASIC RESEARCH www.jasn.org the aorta as determined by Western blotting and no Atrap expression in the vasculature of the kidney as determined by immunostaining. 19 In the kidney, the organ with the highest Atrap expression, Atrap was expressed predominantly in the proximal tubule. This finding is in agreement with another renal localization study 19 ; however, unlike this recent study, we did not find significant tubular Atrap expression in segments other than the proximal tubule, although scattered single cells of the thick ascending limb and the distal convoluted tubule seemed to express Atrap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BASIC RESEARCH www.jasn.org the aorta as determined by Western blotting and no Atrap expression in the vasculature of the kidney as determined by immunostaining. 19 In the kidney, the organ with the highest Atrap expression, Atrap was expressed predominantly in the proximal tubule. This finding is in agreement with another renal localization study 19 ; however, unlike this recent study, we did not find significant tubular Atrap expression in segments other than the proximal tubule, although scattered single cells of the thick ascending limb and the distal convoluted tubule seemed to express Atrap.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with a recent study that addressed the tissue distribution of Atrap by Western blotting. 19 Co-staining with the vascular smooth muscle cell marker SM22 revealed virtually no Atrap expression in blood vessels. This observation is congruent with a report that indicated very low levels of Atrap expression in Figure 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,12 The anti-AT1R antibody (sc-1173) was purchased from Santa Cruz Biotechnology, Inc. 5 Western blot analysis was performed as described previously. 5,6 Briefly, the cell extracts (20 g per lane) or rat tissue extracts (10 g per lane for liver and kidney and 20 g per lane for heart) were used for electrophoresis. Membranes (Millipore) were incubated with either (1) anti-ATRAP antibody or (2) anti-AT1R antibody and subjected to enhanced chemiluminescence (Amersham Biosciences).…”
Section: Western Blot Analysis Of Atrap and At1rmentioning
confidence: 99%
“…3,4 We showed that ATRAP is expressed in many tissues such as the kidney, heart, and liver. 5 Previous studies showed that ATRAP exerts its inhibitory action on AT1R signaling by promoting a constitutive internalization of AT1R and decreasing the cell surface AT1R number. 6,7 In this study, we examined whether the expression of ATRAP is regulated in a tissue-specific manner in spontaneously hypertensive rats (SHR).…”
mentioning
confidence: 99%